Analisis Pemeriksaan Protein Bence Jones pada Urin Lansia dengan Metode Osgood - Untari Untari; Junaiddin Junaiddin (FORIKES, 2022)
The risk factor for the high amount of protein in the urine is age. This study aims to determine the presence or absence of Bence Jones protein in the urine of the elderly in Kladufu Village, Sorong City. This research is an observational study using quantitative methods. A total of 39 urine samples were examined at the Clinical Chemistry Laboratory, STIK Papua. Based on the results of the examination, it is known that there are 25 samples (64%) that do not contain Bence Jones protein (negative), 9 samples (23%) contain Bence Jones protein with a protein content of 0.01-0.1% and 5 samples (12%) contain Bence Jones protein. Bence Jones protein with a concentration of 0.1-0.2%. It was concluded that the number of negative samples was more than positive.Keywords: elderly; proteins; OsgoodABSTRAK Faktor risiko penyebab tingginya jumlah protein dalam urin adalah usia. Penelitian ini bertujuan untuk mengetahui ada tidaknya protein Bence Jones pada urin lansia di Kelurahan Kladufu, Kota Sorong. Penelitian ini adalah penelitian observasional menggunakan metode kuantitatif. Sebanyak 39 sampel urin diperiksa di Laboratorium Kimia Klinik, STIK Papua. Berdasarkan hasil pemeriksaan diketahui bahwa terdapat 25 sampel (64%) tidak mengandung protein bence Jones (negatif), 9 sampel (23%) mengandung protein bence Jones dengan kadar protein 0,01-0,1% dan 5 sampel (12%) mengandung protein bence Jones dengan kadar 0,1-0,2%. Disimpulkan bahwa jumlah sampel negatif lebih banyak daripada positif.Kata kunci: lansia; protein; Osgood